Influence of weed management practices in maize (Zea mays) based intercropping system - SANNAGOUDAR, MANJANAGOUDA S; MURTHY, K N KALYANA; NAGARAJU; RAJANNA, G A; GHOSH, AVIJIT; SINGH, AMIT K; GUPTA, GAURENDRA; KUMAR, R V (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted at University of Agricultural Sciences, Bengaluru during kharif 2016 and 2017 on red sandy loam soil and the experiment was laid out in Randomized Complete Block Design with factorial concept and replicated thrice. There were 15 treatment combinations involving three intercrops and five weed management practices. The results of the experiment revealed that intercropping of maize (Zea mays L.) with cowpea [Vigna unguiculata (L.) Walp.] has recorded significantly lower total weed density (5.92 No./m2), weed dry weight (6.21 g/ m2), higher WCE (66.97 %), lower WI (17.67 %), higher grain yield (5842 kg/ha) and stover yield (7035 kg/ha) but the higher MEY (8224 kg/ha) was recorded in maize + pole bean intercropping system. Among the different weed management practices, pre-emergence application of pendimethalin 30 % EC @ 1.50 kg/ha recorded significantly lower weed population (5.12 No./m2), weed dry weight (5.05 g/m2), higher WCE (81.81 %), lower WI (7.24 %), higher grain (6589 kg/ha), stover yield (8033 kg/ha) and MEY (8860 kg/ha) compared to other weed management practices.